Port State Control Inspections During the COVID Pandemic – Case Study: Republic of Croatia - Peričin, Ljiljana; Vučetić, Šime; Barić, Mate; Milin, Svetko (Transactions on Maritime Science, 2024)
The paper analyzes the Port State Control system established to ensure that ships meet international safety standards, are safe for the environment and provide adequate living and working conditions for the ship's crew. The results of the research on Port State Control inspections of foreign state-owned ships in the waters of the Republic of Croatia are presented, with an emphasis on deficiencies in the safety of navigation. The research was conducted over the three-year period of the COVID pandemic, i.e. from 2019 to 2021. The Thetis and Paris Mou inspection databases were used for analysis. The aim of the analysis was to determine the number of inspections in the ports of the Republic of Croatia, the causes of ship detention and the most common deficiencies in the domain of safety of navigation identified by inspections during the COVID pandemic. Given that safety of navigation is one of the components of the safety system at sea, emphasis was placed on the identification of deficiencies in the area of safety of navigation.